2007
DOI: 10.1097/aud.0b013e3181576738
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Evaluation of a Hearing Aid with Trainable Amplification Parameters

Abstract: In everyday listening situations, aid users can train this prototype aid to provide amplification parameters that, in such situations, they prefer significantly more often than untrained parameters prescribed and adjusted in a clinic. The preference for the trained settings was not significantly affected by the training of the noise suppression strength, and was moderately but not significantly correlated with the hours of aid use during the training period. Therefore, the customization of compression paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 28 publications
(26 reference statements)
2
56
0
1
Order By: Relevance
“…Various prescription methods result in prescription targets that differ from individually preferred gain by up to 10 dB or more, particularly at the high frequencies Keidser et al, 2005;Keidser, O'Brien, Carter, McLelland, & Yeend, 2008;Mueller, 2005;Polonenko, Scollie, & Moodie, 2010;Smeds et al, 2006;Zakis, Dillon, & McDermott, 2007). Other studies have reported that mean preferred overall gain is about 3 to 4 dB less than the prescriptive targets Horwitz & Turner, 1997;Humes, Wilson, Barlow, & Garner, 2002;Keidser, O'Brien, et al, 2008;Marriage et al, 2004;Mueller & Bentler, 2005;Polonenko et al, 2010;Zakis et al, 2007).…”
Section: Pico Question Nomentioning
confidence: 99%
See 4 more Smart Citations
“…Various prescription methods result in prescription targets that differ from individually preferred gain by up to 10 dB or more, particularly at the high frequencies Keidser et al, 2005;Keidser, O'Brien, Carter, McLelland, & Yeend, 2008;Mueller, 2005;Polonenko, Scollie, & Moodie, 2010;Smeds et al, 2006;Zakis, Dillon, & McDermott, 2007). Other studies have reported that mean preferred overall gain is about 3 to 4 dB less than the prescriptive targets Horwitz & Turner, 1997;Humes, Wilson, Barlow, & Garner, 2002;Keidser, O'Brien, et al, 2008;Marriage et al, 2004;Mueller & Bentler, 2005;Polonenko et al, 2010;Zakis et al, 2007).…”
Section: Pico Question Nomentioning
confidence: 99%
“…The evidence showed that on average, prescriptive fittings yield initial responses that are about 3 to 4 dB higher than user preferences Horwitz & Turner, 1997;Humes et al, 2002;Keidser, O'Brien, et al, 2008;Marriage et al, 2004;Mueller & Bentler, 2005;Polonenko et al, 2010;Zakis et al, 2007). Consequently, prescribed gain for both the DSL and NAL-NL methods have been reduced in their latest version (Polonenko et al, 2010).…”
Section: Pico Question Nomentioning
confidence: 99%
See 3 more Smart Citations